Perioperative care practices and outcomes of intracranial neurosurgery: Experience at a dedicated neurosciences hospital in a developing country - Suparna Bharadwaj; Kadarapura Nanjundaiah Gopalakrishna; V S Akash; Subhas Konar; Bharath Srinivasaiah; Sriganesh Kamath (Wolters Kluwer Medknow Publications, 2023)
Background and Aims: Understanding of perioperative care practices and early postoperative outcomes helps minimize potentially preventable perioperative complications while supporting systemic and neurological well-being. The objective of this prospective study was to evaluate the perioperative care practices and early postoperative outcomes of cranial neurosurgery at a high-volume tertiary care neurosciences hospital in India. We also aimed to see if the care elements differed depending on the surgical approach. We hypothesized that care elements and outcomes are likely to be different between major surgical approaches. Material and Methods: This was a prospective observational study of consecutive adult neurosurgical patients who underwent elective surgeries for intracranial pathologies over a period of six months from October 2020 to March 2021 at a tertiary care neurosciences center in India. Perioperative data about intraoperative care elements and early postoperative outcomes till the third day after surgery were collected. Results: Incidence of blood loss >1 L was significantly (P = 0.07) higher after infratentorial surgery (26%, N = 17). Incidence of intraoperative and postoperative desaturation was more after transnasal surgery (6%, N = 2, P = 0.002, and 9%, N = 3, P = 0.01, respectively). Conclusion: This study informs the early perioperative care practices of neurosurgical patients from a dedicated neurosciences hospital in a developing world. We observed that transnasal surgery was associated with more perioperative adverse events and slower convalescence compared to supra- and infratentorial surgeries despite being a considerably less invasive surgery.